THE LOST GENERATION IN AMERICAN LITERATURE: DISILLUSIONMENT, IDENTITY CRISIS, AND MODERNIST EXPRESSION - Iroda Egamberdiyeva Abdurahimovna; Qodirov Izzatillo Xayrullo o‘g‘li (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines the concept of the Lost Generation in American literature, focusing on themes of disillusionment, identity crisis, and modernist expression. The study analyzes how post-World War I writers responded to the trauma of war and the collapse  of  traditional  values,  leading  to  new  literary  forms  and  philosophical perspectives. The research highlights the works of key representatives such as Ernest Hemingway, F. Scott Fitzgerald, and Gertrude Stein, who captured the emotional and psychological instability of the postwar generation. Their works reflect fragmentation, alienation, and the search for meaning in a rapidly changing world. Furthermore, the article  argues  that  the  Lost  Generation  played  a  crucial  role  in  shaping  modernist literature  by  breaking  away  from  traditional  narrative  structures  and  introducing innovative stylistic techniques. The study also emphasizes the cultural and historical significance of this movement in redefining American identity in the twentieth century.